Selective oxidation of manganese in molten pig iron - Pihura, Derviš (Materiali in tehnologije, 2010)
An examination of the process of selective oxidation for molten pig iron indicates the possibility of lowering the content of unwanted or harmful elements. This process makes it possible to achieve the optimum Mn content in pig iron (hot metal) without any oxidation of the other elements present, suchas carbon, etc. Several variants of oxygen blowing with the addition of a slag-forming component were checked. The final element content in the hot metal depends on the initial Mn content, the oxygen blowing and on the added slag components. The lowering of the Mn content in the hot metal to the limit solves the problems of converter processing, lowers the slag quantity, increases the yield of steel by more 4 % and improves the steel-making process.
Keywords: oksidacija; grodelj; žlindra; mangan; jeklo